Indoleamine 2, 3-dioxygenase 1 in corneal endothelial cells limits herpes simplex virus type 1-induced acquired immune response. Issue 10 (3rd July 2015) - Haruki, Tomoko; Miyazaki, Dai; Inata, Koudai; Sasaki, Shin-ichi; Yamamoto, Yukimi; Kandori, Michiko; Yakura, Keiko; Noguchi, Yumiko; Touge, Chizu; Ishikura, Ryoko; Touge, Hirokazu; Yamagami, Satoru; et al.
Abstract : Background: Corneal endothelial cells are known to be targets of herpes simplex virus type 1 (HSV-1) infection; however, the pathogenesis of HSV infections of the endothelial cells has not been definitively determined. The purpose of this study was to examine an unrecognised strategy of corneal endothelial cells to protect themselves from HSV-1 infection. Methods: Immortalised human corneal endothelial cells (HCEn) were infected with HSV-1. Based on the global transcriptional profile, the expression of indoleamine 2, 3-dioxygenase 1 (IDO1) was determined using real-time PCR and western blots. To examine whether IDO1 has any antiviral role, we tested whether viral replication was affected by blocking the activity of IDO1. The immune modulatory role of IDO1 was analysed to determine whether IDO1 might contribute to modulating the recall responses of HSV-1-sensitised CD4 + T cells. Results: IDO1 was strongly expressed in HCEn cells after HSV-1 infection. IDO1 blockade did not significantly restrict viral transcription or replication, arguing against a previously recognised antiviral role for IDO1. When HCEn cells were examined for antigen-presenting function, HSV-1-primed HCEn cells stimulated the proliferation of allogeneic CD4 + T cells and interleukin 10 (IL-10) secretion. When the recall response to HSV-1 was measured by the mixed lymphocyte reaction, the HCEn-stimulated CD4 + T cells modulated and limited the recall response. When IDO1 was silenced in HCEn cells, the HCEn-mediated immune modulatory activity and regulatory T-cell activation were reduced. Overexpression of IDO1 promoted immune modulatory activity, which was partly conveyed by IL-10. Conclusions: IDO1 induced by HSV-1 infection limits and dampens excessive acquired immune responses in corneal endothelial cells.